Novel Role for PD-1:PD-L1 as Mediator of Pulmonary Vascular Endothelial Cell Functions in Pathogenesis of Indirect ARDS in Mice - Lomas-Neira, Joanne; Monaghan, Sean F.; Huang, Xin; Fallon, Eleanor A.; Chung, Chun-Shiang; Ayala, Alfred (Frontiers in Immunology, 2018)
Deficiency of the co-inhibitory receptor, Programmed cell death receptor (PD)-1, provides a survival benefit in our murine shock/sepsis model for the development of indirect acute respiratory distress syndrome (iARDS). Further, of clinical significance, patients that develop ARDS express increased PD-1 on their blood leukocytes. While PD-1 expression and its regulatory role have been associated with mainly T-cell responses, the contribution of its primary ligand, PD-L1, broadly expressed on non-immune cells such as lung endothelial cells (ECs) as well as immune cells, is less well understood. Here we show that a ‘priming insult’ for iARDS, such as non-lethal hemorrhagic shock alone, produced a marked increase in lung EC PD-L1 as well as blood leukocyte PD-1 expression, and when combined with a subsequent ‘trigger event’ (polymicrobial sepsis), not only induced marked iARDS but significant mortality. These sequelae were both attenuated in the absence of PD-L1. Interestingly, we found that gene deficiency of both PD-1 and PD-L1 improved EC barrier function, as measured by decreased bronchoalveolar lavage fluid protein (i.e. lung leak). However, PD-L1 deficiency, unlike PD-1, significantly decreased EC activation through the Angiopoietin/Tie2 pathway in our iARDS mice. Additionally, while PD-1 gene deficiency was associated with decreased neutrophil influx in our iARDS mice, EC monolayers derived from PD-L1 deficient mice showed increased expression of EC junction proteins in response to ex vivo TNF- stimulation. Together, these data suggest that ligation of PD-1:PD-L1 may play a novel role(s) in the maintenance of pulmonary EC barrier regulation, beyond that of the classic regulation of the leukocyte tolerogenic immune response, which may account for its pathogenic actions in iARDS.